A synchronous Alpine and Corsica-Sardinia rotation: new paleomagnetic evidences from the Tertiary Piedmont Basin (NW Italy) - Maffione, M.; Speranza, F.; Faccena, C.; Cascella, A.; Vignaroli, G.; Sagnotti, L. (TRABAJOS DE GEOLOGÍA, 2010)
We report on the paleomagnetism of 34 sites from Lower Oligocene-Middle Miocene sedimentsexposed in the Tertiary Piedmont Basin (TPB, NW Italy). Paleomagnetic directions from 23 sitesshow that the TPB rotated ca. 50° counterclockwise with respect to Africa in Aquitanian-Serravalliantimes. The rotation, likely driven by underneath nappe stacking, was synchronous with (further) bendingof the Alpine chain. Both the rotation magnitude and its timing are similar to those documented for theCorsica-Sardinia microplate, therefore the formation of the western Alpine arc (or part of its present-daycurvature) occurred during the rollback of the Apenninic slab and related back-arc spreading of theLiguro-Provençal Basin, and drift of the Corsica-Sardinia block. This suggests a common dynamics drivingboth the Alpine and the Apennine slab motions. Paleomagnetic data also document that the Adriaticplate has undergone no paleomagnetic rotation since Middle-Late Miocene times.